3 - Moving forward to African Monetary Integration: Lessons from the CFA Franc - Sylla, Ndongo Samba (Africa Development, 2020)
The CFA franc was established in 1945 as a colonial currency. As such, its rationale was to transfer economic surpluses from the French colonies in West and Central Africa to the metropolis. Despite formal decolonisation, this currency shared by 14 countries still performs the same function and remains under the political control of the French government. Recently, the CFA franc has been increasingly challenged by a growing number of African intellectuals and Pan-Africanist social movements demanding its abolition. The objective of this article is to derive lessons about African monetary integration, building on this special but heuristic case. Following a brief history of the CFA franc currency arrangement and a description of its economic shortcomings, this article discusses the options for moving out of the monetary status quo. The author argues that, in the current circumstances, a system of solidary national currencies is the best way forward for African monetary integration.